(untitled) (Annals of Medical Research, 2021)
Aim: Aim of the present study is to indicate the incidence of os fabella in our population and to evaluate the side and gender related differences.Material and Methods: 500 patients (224 females, 276 males) who underwent Magnetic Resonance Imaging (MRI) for various indications were enrolled in the present study. Patients had no history of trauma or surgery. MR images of the patients were evaluated retrospectively.Results: 140 patients with os fabella were reported (28%). 52 of the 140 patients were females (37%) 88 were males (63%). Male predominance in this study was statistically significant. (p= 0.003). Bilaterality incidence of os fabella was 25.71%. There was no statistically significant incidence difference between left and right sides. (p = 0.1005) Difference between genders according to length and width of os fabella was evaluated in 96 patients who underwent bilateral knee MR imaging. Length of right sided os fabella was greater in males than in females (p = 0.003).Conclusion: Proper understanding of anatomy and variations of knee region is important for diagnosis and treatment of patients with knee problems. Os fabella is one of the variations in the knee region which has clinical importance and may cause diagnostic pitfalls and surgical complications.